Meaning and Imagery in Pay Jarot Sujarwo’s “Kekasih, Kemarau Kali Ini Tidak Ada Jingga, Tidak Ada Jingga” and Its Pedagogical Relevance for Literature Courses - Melati, Felisitas Viktoria; Sumarni, Margaretha Lidya; Jewarut, Siprianus; Saputro, Totok Victor Didik (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study aims to analyze the meaning and imagery of Pay Jarot Sujarwo’s poem entitled “Kekasih, Kemarau Kali Ini Tidak Ada Jingga, Tidak Ada Jingga” and to describe its relevance as a teaching material for literature courses. This study uses a qualitative descriptive approach with a structural analysis of the poem’s content. The theoretical framework of this study draws on the structural theory of semiotics to examine the connotative meaning of the imagery and diction and to identify signs pointing to meanings beyond the diction. The results of the study show a diversity of imagery found, including visual, auditory, motion, tactile, and atmospheric imagery. The use of imagery clearly conveys the inner atmosphere of longing and despair. This poem is also relevant to literary learning because it uses diction that trains students to understand implied meanings, imagery that supports the aesthetic analysis of language, and a theme that effectively develops students’ critical thinking skills. This poem can be a model text to improve students’ literary competence.